2014
DOI: 10.1007/s00404-014-3232-6
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide survey of IVF practices: trigger, retrieval and embryo transfer techniques

Abstract: This is the largest and most diversely represented survey of specific IVF practices addressing oocyte maturation triggers, oocyte retrieval and embryo transfers. Several uniform practice patterns were identified that can be correlated with evidence-based medicine; however, we identified multiple variable practice patterns which is likely the result of the absence of definitive evidence to guide IVF practitioners. The results of this survey allow IVF providers to compare their specific practice patterns with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…In analysis of subgroup with irregular anovulatory cycle PCOS, authors reported a development of more severe OHSS when compared to less risk, women with regular ovulatory cycles [8] , so there is a need for adequate powered RCT to explore the antagonist protocol OHSS sparing effect in women at high risk for OHSS development; namely, with high basal Antimullerian hormone (AMH), Antral follicular count (AFC) and high SE2 at ovulation triggering. GnRh agonist ovulation triggering instead of HCG as OHSS protective strategy, despite it is only possible in non-agonist based protocols as antagonist protocols as well as recently introduced progesterone primed ovarian stimulation protocol (PPOS), [30,31,32,33] was less effective than HCG triggering as regards of ongoing pregnancy rate and live birth rate [26] as well as infertility clinician still preferred HCG over GnRh agonist in antagonist protocol [28] and that recent review of utilization of GnRh agonist as ovulation triggering instead of HCG stated that this issue still needs more research [29] .…”
Section: Discussionmentioning
confidence: 99%
“…In analysis of subgroup with irregular anovulatory cycle PCOS, authors reported a development of more severe OHSS when compared to less risk, women with regular ovulatory cycles [8] , so there is a need for adequate powered RCT to explore the antagonist protocol OHSS sparing effect in women at high risk for OHSS development; namely, with high basal Antimullerian hormone (AMH), Antral follicular count (AFC) and high SE2 at ovulation triggering. GnRh agonist ovulation triggering instead of HCG as OHSS protective strategy, despite it is only possible in non-agonist based protocols as antagonist protocols as well as recently introduced progesterone primed ovarian stimulation protocol (PPOS), [30,31,32,33] was less effective than HCG triggering as regards of ongoing pregnancy rate and live birth rate [26] as well as infertility clinician still preferred HCG over GnRh agonist in antagonist protocol [28] and that recent review of utilization of GnRh agonist as ovulation triggering instead of HCG stated that this issue still needs more research [29] .…”
Section: Discussionmentioning
confidence: 99%
“…HCG is the most widely used trigger in current practice, being applied in more than three quarters of cycles ( 6 ). As it shares the same alpha subunit, and has 85% homology of the beta subunit as native LH, hCG activates the LH receptor ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Replacing HCG with gonadotrophin releasing hormone (GnRH) agonist for triggering final oocyte maturation has been proposed for women at high-risk for OHSS, who are pretreated with GnRH antagonist protocols, in combination with freezing all oocytes or embryos (OHSSfree clinic) (Devroey et al, 2011;Youssef et al, 2014). This strategy has gained increasing popularity in recent years (De Ziegler and Shoham, 2013;Tobler et al, 2014), as it can virtually eliminate OHSS development (Humaidan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%